Revision of the genus Smittia Holmgren, 1869 (Diptera Chironomidae Orthocladiinae ), 2nd note (Bollettino di zoologia agraria e bachicoltura, 2024)
A revision of the genus Smittia Holmgren (Diptera Chironomidaesubfamily Orthocladiinae tribe Metriocnemini) is carried out. Three new species,S. abruzzae, S. alpilonga and S. stercoraria are here described, S. alpicola Goetghebuer,1941 is redescribed from type materia!, S. rostrata Goetghebuer inSchmolzer, 1962, previously considered a nomen dubium, is redescribed from typemateri al.Species descriptions are based on adult males morphology, at present no diagnosticcharacter is available to separate adult females, pupae and larvae. A key toidentify the known palearctic species is given.
Keywords: Diptera; Chironomidae; Smittia; taxonomy; new species